2019
DOI: 10.1088/1755-1315/341/1/012070
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of Akhal-Teke horse subpopulations using 17 microsatellite loci

Abstract: Akhal-Teke is the ancient cultural horse breed of oriental origin. The study of genetic features different subpopulations of Akhal-Teke breed was carried out on 17 loci of DNA microsatellites (VHL20, HTG4, AHT4, HMS7, HTG6, AHT5, HMS6, ASB23, ASB2, HTG10, HTG7, HMS3, HMS2, ASB17, LEX3, HMS1 and CA425) to assess their genetic differentiation. The results of DNA typing of 5457 Akhal-Teke horses on 17 microsatellite loci show that gene pool of world population is represented by 121 alleles, among which 98 are fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The 15 autosomal microsatellite markers we applied have been in widespread use since they were recommended for diversity studies by ISAG‐FAO and the International Society for Animal Genetics (Cothran & Luís, 2005; FAO, 2011). Despite the advance of SNP genotyping, very few studies of horses have used SNPs to date for phylogenetic questions (Petersen et al, 2013) and the use of use of 12 to 17 microsatellites for breed analysis remains popular (e.g., Cosenza, La Rosa, Rosati, & Chiofalo, 2019; Isakova et al, 2019; Khanshour, Hempsey, Juras, & Cothran, 2019; Khaudov et al, 2019; Ustyantseva, Khrabrova, Abramova, & Ryabova, 2019; Zeng et al, 2019). The dendrogram of breed relationships analyzed by SNP typing of 36 breeds (Petersen et al, 2013) is almost an exact match of the results from the 15 microsatellite loci, thus suggesting that the results from our 15 microsatellites are robust.…”
Section: Discussionmentioning
confidence: 99%
“…The 15 autosomal microsatellite markers we applied have been in widespread use since they were recommended for diversity studies by ISAG‐FAO and the International Society for Animal Genetics (Cothran & Luís, 2005; FAO, 2011). Despite the advance of SNP genotyping, very few studies of horses have used SNPs to date for phylogenetic questions (Petersen et al, 2013) and the use of use of 12 to 17 microsatellites for breed analysis remains popular (e.g., Cosenza, La Rosa, Rosati, & Chiofalo, 2019; Isakova et al, 2019; Khanshour, Hempsey, Juras, & Cothran, 2019; Khaudov et al, 2019; Ustyantseva, Khrabrova, Abramova, & Ryabova, 2019; Zeng et al, 2019). The dendrogram of breed relationships analyzed by SNP typing of 36 breeds (Petersen et al, 2013) is almost an exact match of the results from the 15 microsatellite loci, thus suggesting that the results from our 15 microsatellites are robust.…”
Section: Discussionmentioning
confidence: 99%
“…The number of different alleles per locus (Na) was a common genetic variation in horse breed based on microsatellite markers. Western Arabian Horse Na varied from 3-5 (Khanshour et al 2013), Iranian horse has Na from 3-4 (Moshkelani et al 2011), Polish Konik Horse has Na varied from 5-6 (Fornal et al 2020), Akhal-Teke horse has Na varied from 3-4 (Ustyantseva et al 2019). Sumbawa-Indonesian horse in this study has a lower number of Na than horse breeds from other regions of the world since these horse breeds only have a maximum of two numbers of alleles per locus.…”
Section: Resultsmentioning
confidence: 68%
“…On average, the Lalar population had more alleles than the Liang population. This result was an early indication of the genetic variation between these populations since a different number of alleles was an essential parameter of genetic variation based on microsatellite marker (Ustyantseva et al 2019). Several parameters were computed to measure genetic variability between the Lalar and Liang populations (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, STR HTG7 is worthy of attention. A low number of alleles in HTG7 (four to six alleles) was recorded in local populations as Akhal-Teke [ 12 , 28 ], Lithuanian Horse [ 7 ], Polish Konig Horse [ 29 ], Colonial Spanish Horse [ 30 ], and Sanfratellano Horse [ 8 ] and in a cosmopolitan breed such as Thoroughbred (four alleles) [ 13 , 31 ]. Additionally, in the present study, HTG7 showed a low number of alleles (from a minimum of four to a maximum of six in the different groups) and a decrease in frequencies of some alleles along the time from the first (1975–90) to the last period (2010–19).…”
Section: Discussionmentioning
confidence: 99%